Comparative Study of Civil Service Reform in Indonesia and Vietnam - Anandar Mulia; Muhammad Aziz Muslim (Khazanah Multidisiplin, 2025)
This study aims to compare the civil servant (Aparatur Sipil Negara, ASN) management system reforms in Indonesia and Vietnam, focusing on four key aspects: recruitment, compensation, performance measurement, and promotion. A comparative analysis approach was employed, involving qualitative analysis of existing policies and practices in both countries. The findings indicate that both countries have adopted meritocracy principles in ASN reforms, though the approaches and challenges faced differ. Indonesia excels in the utilization of digital technology, job competency standards, and performance measurement applications, while Vietnam continues to face challenges in political patronage and aligning remuneration and promotions with performance outcomes. Both countries show a shift toward performance-based compensation systems, with Vietnam starting to implement a job coefficient-based payment model. Indonesia's performance measurement is more integrated through systems like SAKIP and e-Kinerja, while Vietnam relies on qualitative evaluations based on specific criteria. Promotion reforms in both countries aim to strengthen objectivity, although political influence remains more prominent in Vietnam. These results contribute to the understanding of how merit-based reforms can be implemented in different political and administrative contexts, providing practical and theoretical implications for public administration. However, the study has certain limitations, such as the scope of qualitative data and country-specific contexts, which should be addressed in future research. Based on these findings, further studies should explore how political influences can be minimized to enhance the effectiveness of merit-based reforms in public administration systems.